The Cost of Air Pollution in Lagos - Croitoru, Lelia (World Bank, Washington, DC, 2019)
Lagos, Nigeria’s commercial capital is one of the world’s fastest growing megacities, but many are breathing polluted air. This report estimates that in 2018, air pollution caused more than 11,200 premature deaths in Lagos. Children under five are the most affected accounting for about sixty percent of the deaths. The health cost of air pollution was estimated at 2.1 billion US dollars, corresponding to about 2.1 percent of Lagos state’s gross domestic product (GDP).